2018
DOI: 10.1002/ange.201809463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Conformation‐Dependent Mechanoluminescence: Same Mechanical Stimulus but Different Emissive Color over Time

Abstract: Ap henothiazine derivative of FCO-CzS with changeable mechanoluminescence is reported, which,u pon continuous mechanical stimulus,s hows mechanoluminescent emission from blue to white and yellow.Careful analysis of the experimental results,c oupled with the well-understood photoluminescence theory,s how that the molecular conformation transition of the phenothiazine group from quasi-axial to quasi-equatorial is responsible for this dynamic mechanoluminescence effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 45 publications
0
11
1
1
Order By: Relevance
“…Li et al recently demonstrated the dynamic TL color change of phenothiazine/4-fluorobenzophenone integrated molecule under the continuous mechanical stimulus, which was reasoned by the changed molecular conformation and corresponding PL behavior. 10 However, describing TL with general photophysical parameters such as emission efficiency and decay lifetimes is still quite rare and challenging due to the ambiguous aspects of fracture generation and applied force.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al recently demonstrated the dynamic TL color change of phenothiazine/4-fluorobenzophenone integrated molecule under the continuous mechanical stimulus, which was reasoned by the changed molecular conformation and corresponding PL behavior. 10 However, describing TL with general photophysical parameters such as emission efficiency and decay lifetimes is still quite rare and challenging due to the ambiguous aspects of fracture generation and applied force.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10.1021/acs.jpcc.9b08349. Synthetic methods; detailed shock-tube setup; powder XRD patterns and emission spectra before/after experiments; shock wave theory; PL peak intensity and spectral ratio under air/nitrogen; temperature in the pressure chamber; TL/PL lifetimes under atmospheric/ decompressed conditions (PDF)…”
mentioning
confidence: 99%
“…The emission properties that depend on the molecular conformation often change the emission colour upon mechanical stimulation. 32,34,45,46 The application of molecules showing such stimulation-induced phenomena to white light-emitting devices will naturally be limited. Therefore, a promising approach would be to make molecules with no remarkable colour change even under stimulation.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…2017 年, Li 等 [56] 报道了首例同时具备 [57] 还报道了颜色可变的 ML 分 子 FCOCzS, 在连续的机械刺激下, 其动态机械发光从 蓝色到白色再到黄色, 这种独特的动态 ML 效应可归因 于机械刺激下分子构象的改变. 分子间较强的相互作用 限制晶体在机械刺激下的坍塌和滑移, 并使其具有良好 的机械稳定性.…”
Section: 分子排列对力致发光的影响unclassified